Pelatihan Forum Pemangku Kepentingan 1 Provinsi Jawa Barat Program Sekolah Penggerak - Hendro Prasetyono (Jurnal Pengabdian Masyarakat Formosa, 2022)
The theme of this activity is building dreams, making strategies to realize dreams and followup plans. The purpose of this training is that stakeholders are able to reflect on the achievements of educational progress in their area at the end of the semester, have a follow-up plan and commitment to improve the quality of education in their area and can interact and collaborate with each other. The training participants were representatives of the Bekasi City education office, the Education Quality Assurance Institute, school principals, teacher representatives, parents representatives, community representatives and student representatives with a total of 116 participants. The method of implementing the activities uses focus group discussions which are packaged in the form of interactive discussion and question and answer. Implementation of activities at the Patriot Hall of Bekasi City, West Java. Activities arranged in exposure sessions and question and answer sessions to gain knowledge and insight about stakeholders owned by the school to improve the quality of learning. The output of the training activity is that the participants get a follow-up plan and commitment to improve the quality of education in their area